The influence of Tiktok eWOM on consumer purchase intentions for local skincare products - Saphira, Karin Dwi; Widiyanesti, Sri (Keynesia : International Journal of Economy and Business, 2024)
This study investigates how TikTok electronic Word-of-Mouth (eWOM) impacts consumer purchase intentions in Indonesia, focusing specifically on key information characteristics within the local skincare product market. It examines factors such as information quality, information credibility, information task-fit, needs of information, attitude towards information, information usefulness, and information adoption towards purchase intention. Data were gathered from 385 participants via a questionnaire and analyzed using structural equation modeling (SEM) with the partial least squares (PLS) method. The results reveal that information quality, information task-fit, needs of information, attitude towards information, information usefulness, and information adoption significantly influence consumer purchase intentions. These findings underscore the influential role of TikTok in enhancing consumer engagement and shaping purchasing behaviors, particularly in the context of skincare products. For marketers in the skincare industry, these insights are crucial as they highlight the effectiveness of leveraging TikTok and similar platforms for marketing strategies. By understanding these dynamics, marketers can effectively harness social media to engage with consumers, build brand loyalty, and drive purchase decisions in a competitive market landscape.